Mga tinig mula sa ibaba kasaysayan ng Partido Komunista ng Pilipinas at Partido Sosialista ng Pilipinas sa awit, 1930-1955 - Maceda, Teresita Gimenez- (University of the Philippines Press and UP Center for Integrative and Development Studies, Peace, Conflict Resolution and Human Rights Program, 1996)
History of Philippines Communist Party and Philippines Socialist Party in songs.